Colistin neurotoxicity mimicking Guillain-Barré syndrome in a patient with cystic fibrosis: case report and review. Issue 9 (13th September 2021) - Camargo, Celeste; Narula, Tathagat; Jackson, Daniel A; Padro, Teresa; Freeman, W David
ABSTRACT: Guillain-Barré syndrome (GBS) is an immune-mediated polyneuropathy, which is characterized by areflexia and ascending paresthesia which can progress to a respiratory failure. Certain conditions, such as vasculitis and heavy metal and drug toxicity, may have misleadingly similar clinical presentation to GBS. We describe a case of a patient with cystic fibrosis and intravenous colistin-induced neurotoxicity mimicking GBS. The patient had used inhaled colistin on five occasions with no adverse effects, however, developed symptoms on the second day of intravenous treatment. Overlapping findings between immune-mediated polyneuropathy and drug-induced neurotoxicity include limb paresthesia and decreased reflexes. Perioral tingling, however, is a common presentation of colistin-induced neurotoxicity, and therefore, is an important differentiating factor. Early diagnosis prevents further neurologic decline, extensive unnecessary workup and potentially harmful incorrect management.